Method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using rotation process
By covering LLZO and glass phase materials on the surface of NCM positive electrode particles, short-term high-temperature pulses are generated using the rotation process to form glass phase layer and LLZO cladding layer, the problems of the existing positive electrode particles' interface side reaction and low conductivity are solved, and the problem of existing positive electrode particles is achieved. More efficient lithium-ion pathways and battery stability.
Patent Information
- Application Number
- CN202411356043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-05
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-18
AI Technical Summary
The interface of existing positive electrode particles is prone to side reactions, resulting in a decrease in battery life, low electronic conductivity, and poor overall battery performance.
The rotating process is used to coat the surface of the NCM positive electrode particles with LLZO and glass phase materials. Through the short-term high-temperature pulses generated under high-speed rotation, the glass phase material reacts to form a solid electrolyte, forming a glass phase layer to prevent direct contact with the electrolyte, and The NCM large particles were coated with LLZO fine particles to improve the pathway of lithium ions.
Effectively reduce interfacial side reactions, improve lithium ion paths, improve rate charge and discharge performance, enhance the mechanical properties of the positive electrode particles, reduce crushing, and form a more complete electron conduction path through the coating of nanocarbon tubes and amorphous carbon, improving The conductivity and stability of the overall battery.
Smart Images

Figure CN119480873A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials, and in particular to a method for manufacturing NCM positive electrode particles coated with LLZO and a glass phase by using a rotation process. Background Art
[0002] In order to increase the conductivity, a plurality of positive electrode particles are usually filled in the positive electrode slurry, wherein the material of the positive electrode particles can be selected from NCM (lithium nickel cobalt manganese oxide), LMFP (lithium iron manganese phosphate), etc. or a mixture thereof, and the positive electrode particles are distributed in the positive electrode slurry. However, the interface of the positive electrode particles in the prior art is prone to side reactions, which reduces the service life of the positive electrode, and the electronic conductivity is low, so the overall battery performance is poor.
[0003] In order to improve the coating integrity, it is necessary to coat the surface of the positive electrode particles with a glass phase layer. The common method of making a glass phase layer is through melting and quenching at high temperature, and adjusting the heat treatment conditions so that the lattice of the material cannot be arranged in an orderly manner at room temperature. However, this method is more suitable for glass phase layer oxide materials that can withstand long-term heating, such as garnet, perovskite, or phosphate; on the contrary, for glass phase layer non-oxide materials with poor high temperature resistance, such as halide systems and sulfide systems, excessive heating and insulation time will reduce their lithium ion conductivity.
[0004] Therefore, this case hopes to propose a method for manufacturing NCM positive electrode particles coated with LLZO and glass phase using a rotation process. By exchanging the energy generated when the glass phase solid electrolyte precursor collides with the surface of the NCM particles at high speed, a short-term high-temperature pulse is created, causing the precursor to react to produce a glass phase solid electrolyte. Since the area of this instantaneous high temperature effect is only local, the time is short, and the temperature drops quickly, it can prevent the degradation of material properties caused by long-term high temperature. At the same time, by changing the process parameters, this method is also applicable to oxide system electrolytes. Summary of the invention
[0005] Therefore, the purpose of this invention is to solve the problems in the above-mentioned known technologies. This invention proposes a method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process, which is to coat the glass phase material on the surface of the NCM large particles to form the glass phase layer, which can prevent the direct contact between the NCM large particles and the electrolyte and reduce the interface side reaction; at the same time, it reduces the interface impedance of lithium ions entering and exiting the NCM large particles, improves the rate charge and discharge performance, and the existence of the glass phase layer can accommodate the volume change of charge and discharge, improve the mechanical properties of the powder, and reduce breakage. And the NCM large particles are coated with a large number of LLZO fine particles. The LLZO fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed by guiding the dispersed LLZO fine particles, so the design of the positive electrode in this case can make lithium ions have a better path. In this case, carbon nanotubes and the nano-level amorphous carbon are coated on the outside of the NCM large particles coated with LLZO fine particles. The electrons can be conducted on the composite NCM large particles and the nano-scale amorphous carbon can fill the gaps formed by the multiple carbon nanotubes, forming a more complete electron conduction path. The structure of this case can provide stability for the overall positive electrode slurry structure, so the amount of cobalt used can be reduced.
[0006] To achieve the above-mentioned purpose, the invention proposes a method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process, wherein the positive electrode particles are present in the positive electrode of a solid-state or quasi-solid-state battery, wherein the process of the positive electrode particles comprises the following steps: Step 510: Take NCM (nickel cobalt manganese oxide) material, wherein the NCM material is a plurality of NCM large particles, wherein the NCM large particles are in an irregular cubic shape; place the NCM large particles and the glass phase material into a first mixer at the same time, and stir them fully by high-speed rotation so that the two are evenly mixed. Under high-speed rotation, the glass phase material will be fully or partially attached to the surface of the NCM large particles to form a glass phase layer, that is, the NCM large particles with a glass phase layer are formed as a whole; wherein the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction; and at the same time reduce the interface impedance of lithium ions entering and leaving the NCM large particles; the glass phase material has a lithium ion conduction rate higher than 10 -5 S / cm amorphous oxide or non-oxide solid electrolyte; step 510: mixing LLZO (lithium lanthanum zirconium oxide) material with the NCM large particles with a glass phase layer, wherein the LLZO material is a plurality of LLZO fine particles; placing the NCM large particles with a glass phase layer and the LLZO fine particles into a second mixer at the same time and applying high-speed rotation to fully stir them so that they are evenly mixed, and under high-speed rotation, the LLZO fine particles are distributed in the glass phase layer or on the surface of the glass phase layer, and a plurality of composite NCM large particles are formed as a whole.
[0007] The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process further comprises step C:
[0008] The plurality of composite NCM large particles, a plurality of CNTs (Carbon Nanotubes) and a plurality of nano-scale amorphous carbons are mixed to form positive electrode particles coated with carbon materials.
[0009] The following description will provide a further understanding of the features and advantages of the present invention. Please refer to the attached drawings while reading. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 A flowchart showing the manufacturing process of the positive electrode particles in this case.
[0011] Figure 2 A diagram showing the structure of the positive electrode particles in this case.
[0012] Figure 3 Shows the structural diagram of the positive electrode in this case.
[0013] Figure 4 A structural diagram showing the large composite NCM particles in this case.
[0014] Figure 5 A structural diagram showing the large composite NCM particles in this case.
[0015] Figure 6 A structural diagram showing the large composite NCM particles in this case. DETAILED DESCRIPTION
[0016] The structural composition of the present invention, as well as the effects and advantages it can produce, are described in detail below with reference to the drawings and a preferred embodiment of the present invention.
[0017] Please refer to Figures 1 to 6 As shown, the method of applying a rotation process to manufacture NCM positive electrode particles coated with LLZO and a glass phase is shown in the present invention.
[0018] like Figure 3 As shown, a positive electrode 100 of a general solid-state or quasi-solid-state battery comprises:
[0019] a positive electrode substrate 10;
[0020] A positive electrode slurry layer 12 is coated on the positive electrode substrate 10, wherein the positive electrode slurry layer 12 comprises:
[0021] A positive electrode slurry 14 containing a binder, wherein the binder is, for example, PVDF (polyvinylidene difluoride), PEO (poly(ethylene oxide)), and the like.
[0022] The positive electrode particles 200 account for 80 wt % to 98 wt % of the positive electrode slurry layer 12 .
[0023] The process of the positive electrode particles 200 (please refer to Figure 1 ) includes the following steps:
[0024] Step 500: Take NCM (nickel cobalt manganese oxide) material, wherein the NCM material is a plurality of NCM large particles 22, the size of which is 3 microns to 5 microns; it is a single crystal structure (single crystal). The NCM large particles 22 are irregular cubic shapes.
[0025] The NCM large particles 22 and the glass phase material are placed in a first mixer 50 at the same time (such as a three-dimensional mixer or a flat rolling mixer (which is a dry mixer) or a DC impeller mixer (which is a wet mixer, in which solvents such as anhydrous alcohol or isopropyl alcohol are added)) and are fully stirred by high-speed rotation so that the two are evenly mixed, wherein the rotation speed of the first mixer 50 is 50rpm to 3000rpm, and the stirring time is 10 minutes to 12 hours. Oxygen or dry air can be introduced during the mixing process (i.e., under atmosphere protection), which is used to protect the NCM large particles 22 during high-speed rotation to prevent the NCM large particles 22 from decomposing at high temperatures. The oxygen or dry air is added at a speed of 0.5 liters / minute to 5 liters / minute. Under high-speed rotation, the glass phase material will be fully or partially attached to the surface of the NCM large particles 22, and the NCM large particles 22 are coated with a glass phase layer 25 formed by the glass phase material, that is, the NCM large particles 250 with a glass phase layer are formed as a whole. The glass phase layer 25 has a thickness ranging from 5 nanometers to 100 nanometers.
[0026] The glass phase layer 25 is made of a material having a lithium ion conductivity higher than 10 -5 S / cm amorphous oxide or non-oxide solid electrolyte. For example: lithium and IIIA, IVA, VA group oxides (such as: Li2O-RO x, R=B (boron), Al (aluminum), Si (silicon), Ge (germanium), P (phosphorus), As (arsenic), etc., x=1 to 3), or lithium halide / halogen-oxide (such as Li-MO, where M is at least one of the halogens F (fluorine), Cl (chlorine), Br (bromine), I (iodine)), or lithium-sulfide (such as: Li2S-P2S5), or an amorphous oxide-based solid electrolyte (such as an amorphous perovskite-based solid electrolyte (LLTO), a garnet-based solid electrolyte (LLZO), or at least one of lithium-phosphorus-oxygen-nitride (LiPON).
[0027] The glass phase layer 25 can prevent the direct contact between the NCM large particles 22 and the electrolyte, reducing the interface side reactions; at the same time, it can reduce the interface impedance of lithium ions entering and exiting the NCM large particles 22, improve the rate charge and discharge performance, and the existence of the glass phase layer 25 can accommodate the volume changes during charge and discharge, improve the mechanical properties of the powder, and reduce breakage.
[0028] Step 510: LLZO (lithium lanthanum zirconium oxide) material (such as Li 6.2 Ga 0.8 La3Zr2O 12 (Gallium-doped lithium lanthanum zirconium oxide)) is mixed with the NCM large particles 250 having a glass phase layer by high-speed rotation, wherein the LLZO material is a plurality of LLZO fine particles 24, and the maximum radial dimension of the LLZO fine particles 24 is less than 40 nanometers.
[0029] The NCM large particles 250 with the glass phase layer and the LLZO fine particles 24 are simultaneously placed in a second mixer 52 (such as a three-dimensional mixer or a flat rolling mixer) and are fully stirred by high-speed rotation to make them uniformly mixed, wherein the rotation speed of the second mixer 52 is 50rpm to 3000rpm, and the stirring time is 10 minutes to 12 hours. Oxygen or dry air can be introduced during the mixing process (i.e., under atmosphere protection), which is used to protect the NCM large particles 22 during high-speed rotation to prevent the NCM large particles 22 from decomposing at high temperatures. The oxygen or dry air is added at a speed of 0.5 liters / minute to 5 liters / minute. Under high-speed rotation, the LLZO fine particles 24 are distributed in the glass phase layer 25 or on the surface of the glass phase layer 25, and the whole forms a plurality of composite NCM large particles 20 (such as Figure 4 ).
[0030] The LLZO in the LLZO fine particles 24 is preferably selected from at least one of Ga-LLZO (gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (strontium-doped lithium lanthanum zirconium oxide) and Al-LLZO (aluminum-doped lithium lanthanum zirconium oxide).
[0031] Preferably, the LLZO is selected from Cu a X b -LLZO (copper-doped lithium lanthanum zirconium oxide), X is selected from Ga (gallium), Ta (tantalum), Sr (strontium), Ba (barium), Al (aluminum), where a+b = 0.25 to 0.8, a>0.1; the technology of using copper doping in LLZO is quite difficult, but it can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased and the manufacturing cost is relatively cheap. And when the material is exposed to air, the formation of lithium carbonate is reduced. That is, the surface stability of the entire material during sintering is increased.
[0032] In a single NCM positive electrode particle coated with LLZO and a glass phase, the total weight of all the LLZO fine particles 24 is between 0.2 wt % and 2 wt % of the weight of the NCM large particle 250 having a glass phase layer.
[0033] Step 520: The plurality of composite NCM large particles 20, the plurality of CNTs 30 (Carbon Nanotubes) and the plurality of nano-scale amorphous carbons 35 are mixed to form carbon-coated positive electrode particles 300. There are two mixing methods, which are described as follows:
[0034] Step 520A: The plurality of composite NCM large particles 20, the plurality of CNTs 30, and the plurality of nano-scale amorphous carbons 35 are simultaneously placed in a dry mixer 55 (such as a planetary mixer or a drum mixer) for mixing, so that the CNTs 30 and the nano-scale amorphous carbons 35 cover the composite NCM large particles 20 to form carbon-coated positive electrode particles 300 (such as Figure 1 ). The stirring speed of the dry stirrer 55 is 50 rpm to 500 rpm, and the stirring time is 2 hours to 8 hours.
[0035] The nano-scale amorphous carbon 35 is such as super P. The size of the nano-scale amorphous carbon 35 is between 20 nanometers and 100 nanometers. Each of the nano-scale amorphous carbon 35 is mainly located between the gaps formed by the interlacing of the plurality of CNTs 30 (such as Figure 2). The total volume weight of the nano-scale amorphous carbon 35 accounts for a ratio of 0.1 wt % to 2 wt % of the weight of a single composite NCM large particle 20.
[0036] Alternatively, step 510 is followed by step 520B.
[0037] Step 520B: The CNT 30 is first mixed with the plurality of composite NCM large particles 20, and then mixed with the nano-scale amorphous carbon 35 to form the carbon-coated positive electrode particles 300. The CNT 30 is first mixed with the plurality of composite NCM large particles 20 by dry ball milling or wet ball milling:
[0038] The dry ball milling mixing is to place the CNT 30 and the plurality of composite NCM large particles 20 into a dry ball mill 57 for ball milling. The rotation speed of the dry ball mill 57 is between 50 rpm and 1000 rpm. The mixing time is between 20 minutes and 12 hours. The ball milling is performed at room temperature to 50 degrees.
[0039] Another mixing method is wet ball milling, where the CNT 30 is dispersed in a dispersant and then placed in a wet ball mill 56 with the plurality of composite NCM large particles 20 for wet ball milling. The speed of the wet ball mill 56 is between 50 rpm and 500 rpm, and the mixing time is between 20 minutes and 12 hours. The dispersant is selected from a polar or non-polar non-aqueous organic solvent.
[0040] After the CNT 30 and the plurality of composite NCM large particles 20 are mixed by any of the ball milling methods, the nano-scale amorphous carbon 35 is added and mixed, so that the CNT 30 and the nano-scale amorphous carbon 35 cover the composite NCM large particles 20 to form the carbon-coated positive electrode particles 300.
[0041] The CNT 30 includes short-chain CNT 32 and long-chain CNT 34. The length of the short-chain CNT 32 is between 0.5 micrometers and 1 micrometer, and the length of the long-chain CNT 34 is between 3 micrometers and 8 micrometers. The total weight of the CNT 30 accounts for 0.1 wt% to 2 wt% of the weight of the single NCM large particle 22.
[0042] The CNT 30 can form different levels of cross-connections on the composite NCM large particle 20. When more carbon nanotubes 30 are added, the conductivity of the entire composite NCM large particle 20 will be improved. Figure 5 and 6As shown, the short-chain CNT 32 is used to bridge the LLZO fine particles 24 and the NCM large particles 22. The long-chain CNT 34 is used to cover the composite NCM large particles 20. CNT is a very good conductive material. When it is attached to the composite NCM large particles 20, it forms a shape like a ball of wool (such as Figure 2 ).
[0043] The carbon nanotubes 30 (i.e., CNT 30) are used to increase the electronic conductivity, that is, to form conductive bridges around the various LLZO fine particles 24, so that electrons can be conducted on the composite NCM large particles 20. The carbon nanotubes 30 are randomly distributed on the surface of the composite NCM large particles 20. Because the carbon nanotubes have extremely high conductivity, electrons can be conducted between the different LLZO fine particles 24 and the NCM large particles 22 through the carbon nanotubes, thereby increasing the conductivity of the entire positive electrode 100 as a whole.
[0044] The nano-scale amorphous carbon 35 is a conductive agent like the CNT 30. Since the nano-scale amorphous carbon 35 is in the form of particles, and the carbon nanotubes 30 are in the form of long strips, gaps are formed between the criss-crossed carbon nanotubes 30, and these gaps cannot conduct current. Therefore, adding the nano-scale amorphous carbon 35 to the gaps can allow the charge to be conducted to the next carbon nanotube 30 through the bridging of the nano-scale amorphous carbon 35, thereby further increasing the current transmission.
[0045] In the present case, (the CNT 30+the nano-scale amorphous carbon 35):the single composite NCM particle 20 (ie, the NCM large particle containing LLZO and having a glass phase layer)=(0.09 to 3):100 (weight ratio).
[0046] The CNT 30: the nano-scale amorphous carbon 35: the single composite NCM large particle 20 = 0.5:1:100 (weight ratio).
[0047] After the stirring in steps 510 to 520, the NCM large particles 22 have a size of 3 to 5 microns, the lateral size (i.e., the size along the spherical surface) of the LLZO fine particles 24 is between 50 nanometers and 300 nanometers, and the size of the nano-scale amorphous carbon 35 is between 20 nanometers and 100 nanometers.
[0048] The advantage of using carbon nanotubes in this case is that lithium ions can be easily stabilized between the carbon nanotubes, so the positive electrode slurry in this case can stabilize a large number of lithium ions, thereby improving the overall conductivity of lithium ions, and electrons can be easily fixed between the short-chain carbon nanotubes, thereby improving the overall conductivity of lithium ions. In addition, because the ion conductivity is very high, it helps the rapid charging and rapid discharge of the entire battery, and can also reduce the use of cobalt, reducing the overall production cost.
[0049] The advantage of this case is that the glass phase material is coated on the surface of the NCM large particles to form the glass phase layer, which can prevent the direct contact between the NCM large particles and the electrolyte and reduce the interface side reaction; at the same time, the interface impedance of lithium ions entering and leaving the NCM large particles is reduced, the rate charge and discharge performance is improved, and the existence of the glass phase layer can accommodate the volume change of charge and discharge, improve the mechanical properties of the powder, and reduce breakage. The NCM large particles are coated with a large number of LLZO fine particles. The LLZO fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed by the guidance of the dispersed LLZO fine particles, so the design of the positive electrode in this case can make lithium ions have a better path. In this case, nanocarbon tubes and nano-scale amorphous carbon are coated on the outside of the NCM large particles coated with LLZO fine particles. This allows electrons to be conducted on the composite NCM large particles and each nano-scale amorphous carbon can be filled in the gaps formed by the interlacing of the multiple nanocarbon tubes to form a more complete electron conduction path. The structure of this case can provide stability for the overall positive electrode slurry structure, thereby reducing the amount of cobalt used.
[0050] In summary, the humanized and considerate design of this case is quite in line with actual needs. Its specific improvement of existing deficiencies is obviously a breakthrough in progress compared to the known technology, and it does have an improvement in efficacy, which is not easy to achieve. This case has not been published or disclosed in domestic and foreign literature and markets, and has complied with the provisions of the Patent Law.
[0051] The above detailed description is a specific description of a feasible embodiment of the present invention, but the embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or change that does not deviate from the technical spirit of the present invention should be included in the patent scope of this case.
Claims
1. A method for manufacturing NCM positive electrode particles coated with LLZO and glass phase using a rotation process, characterized in that: The positive electrode particles are present in the positive electrode of a solid-state or quasi-solid-state battery, and the process of preparing the positive electrode particles comprises the following steps: Step 510: Take NCM material, i.e., nickel cobalt manganese oxide lithium material, wherein the NCM material is a plurality of NCM large particles, wherein the NCM large particles are in an irregular cubic shape; place the NCM large particles and the glass phase material into a first mixer at the same time, and stir them fully by high-speed rotation so that the two are evenly mixed. Under high-speed rotation, the glass phase material will be fully or partially attached to the surface of the NCM large particles to form a glass phase layer, that is, the NCM large particles with a glass phase layer are formed as a whole; wherein the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction; and at the same time reduce the interface impedance of lithium ions entering and leaving the NCM large particles; the glass phase material has a lithium ion conduction rate higher than 10 -5 S / cm amorphous oxide or non-oxide solid electrolyte; Step 510: Mix the LLZO material with the NCM large particles having a glass phase layer, wherein the LLZO material is a lithium lanthanum zirconium oxide material, wherein the LLZO material is a plurality of LLZO fine particles; place the NCM large particles having a glass phase layer and the LLZO fine particles into a second mixer at the same time and rotate them at high speed to fully stir them so that they are evenly mixed. Under high-speed rotation, the LLZO fine particles are distributed in the glass phase layer or on the surface of the glass phase layer, and a plurality of composite NCM large particles are formed as a whole.
2. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: The size of the NCM large particles is 3 to 5 microns; it is a single crystal structure; The glass phase layer has a thickness between 5 nanometers and 100 nanometers; In step 510, the maximum radial dimension of the LLZO fine particles is less than 40 nanometers.
3. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: Wherein in step 500, the first mixer is selected from a three-dimensional mixer or a flat rolling mixer; or a DC impeller mixer; The DC impeller mixer is added with anhydrous alcohol or isopropanol solvent and stirred sufficiently to make the two evenly mixed.
4. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: In step 500, the rotation speed of the first mixer is 50 rpm to 3000 rpm, and the stirring time is 10 minutes to 12 hours; oxygen or dry air is introduced during the mixing process to protect the NCM large particles during high-speed rotation and prevent the NCM large particles from decomposing at high temperatures; the oxygen or dry air is added at a speed of 0.5 liters / minute to 5 liters / minute.
5. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: The glass phase material is selected from lithium and oxides of Groups IIIA, IVA, and VA, or lithium halides / halogen-oxides, or lithium-sulfides, or amorphous oxide-based solid electrolytes, amorphous perovskite-based solid electrolytes, garnet-based solid electrolytes, or at least one of lithium-phosphorus-oxygen-nitrides.
6. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: The glassy phase material is selected from Li2O-RO x , wherein R is at least one of boron, aluminum, silicon, germanium, phosphorus, and arsenic, and x=1 to 3; Li-MO, wherein M is at least one of the halogens of fluorine, chlorine, bromine and iodine; Li2S-P2S5; LLTO; LLZO; LiPON; At least one of the above.
7. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: The LLZO in the LLZO fine particles is selected from at least one of gallium-doped lithium lanthanum zirconium oxide compounds, copper-doped lithium lanthanum zirconium oxide compounds, tantalum-doped lithium lanthanum zirconium oxide compounds, strontium-doped lithium lanthanum zirconium oxide compounds and aluminum-doped lithium lanthanum zirconium oxide compounds.
8. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: Wherein the LLZO is selected from Cu a X b -LLZO, i.e. copper-doped lithium lanthanum zirconium oxide, X is selected from at least one of gallium, tantalum, strontium, barium and aluminum, wherein a+b=0.25 to 0.8 and a>0.1; using copper-doped LLZO can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased with relatively low manufacturing cost; and when the material is exposed to air, the formation of lithium carbonate is reduced; that is, the surface stability of the entire material during sintering is increased.
9. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: In a single NCM positive electrode particle coated with LLZO and a glass phase, the total weight of all the LLZO fine particles is between 0.2 wt % and 2 wt % of the weight of the NCM large particle with a glass phase layer.
10. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: In step B, the rotation speed of the second mixer is 50 rpm to 3000 rpm, the stirring time is 10 minutes to 12 hours, and oxygen or dry air is introduced during the mixing process to protect the NCM large particles during high-speed rotation and prevent the NCM large particles from decomposing at high temperatures; the oxygen or dry air is added at a speed of 0.5 liters / minute to 5 liters / minute.
11. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 1, characterized in that: The step 520 is also included: The plurality of composite NCM large particles, a plurality of CNTs and a plurality of nano-scale amorphous carbons are mixed to form positive electrode particles coated with carbon materials; CNTs are carbon nanotubes.
12. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The carbon material mixing method is as follows: the multiple composite NCM large particles, the multiple CNTs and the multiple nano-scale amorphous carbons are placed in a dry mixer for mixing at the same time, so that the CNTs and the nano-scale amorphous carbons cover the composite NCM large particles to form the positive electrode particles of the coated carbon material; the stirring speed of the dry mixer is 50 rpm to 500 rpm, and the stirring time is 2 hours to 8 hours.
13. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The carbon material mixing method is: firstly mix the CNT with the multiple composite NCM large particles, and then mix it with the nano-scale amorphous carbon to form the positive electrode particles coated with the carbon material; wherein the CNT is first mixed with the multiple composite NCM large particles by dry ball milling mixing or wet ball milling mixing.
14. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 13, characterized in that: The dry ball milling mixing method is to first directly place the CNT and the plurality of composite NCM large particles into a dry ball mill for ball milling, the dry ball mill has a rotation speed of 50 rpm to 1000 rpm, the mixing time is between 20 minutes and 12 hours, and the ball milling is performed at room temperature to 50 degrees; Then, the nano-scale amorphous carbon is added and mixed, so that the CNT and the nano-scale amorphous carbon cover the composite NCM large particles to form the positive electrode particles of the coated carbon material.
15. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 13, characterized in that: The wet ball milling method is to first disperse the CNT in a dispersant and then place the CNT and the plurality of composite NCM large particles into a wet ball mill for wet ball milling. The wet ball mill has a rotation speed of 50 rpm to 500 rpm and a mixing time of 20 minutes to 12 hours; wherein the dispersant is selected from a polar or non-polar non-aqueous organic solvent; Then, the nano-scale amorphous carbon is added and mixed, so that the CNT and the nano-scale amorphous carbon cover the composite NCM large particles to form the positive electrode particles of the coated carbon material.
16. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The size of the nano-scale amorphous carbon is between 20 nanometers and 100 nanometers; each of the nano-scale amorphous carbon is mainly located between the gaps formed by the interlacing of the plurality of CNTs; The total volume weight of the nano-scale amorphous carbon accounts for a proportion of 0.1 wt % to 2 wt % of the weight of a single composite NCM large particle.
17. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The CNTs are short-chain CNTs and long-chain CNTs, the short-chain CNTs are between 0.5 microns and 1 micron in length, and the long-chain CNTs are between 3 microns and 8 microns in length; the short-chain CNTs are used to bridge the LLZO fine particles and the NCM large particles; the long-chain CNTs are used as a whole to cover the composite NCM large particles.
18. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The ratio of the total weight of the CNT to the weight of a single NCM large particle is between 0.1 wt % and 2 wt %.
19. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: Wherein, (the CNT+the nano-scale amorphous carbon):single composite NCM particle=(0.09 to 3):100, which is a weight ratio.
20. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a rotation process according to claim 11, characterized in that: The CNT: the nano-scale amorphous carbon: the single composite NCM large particle = 0.5:1:100, which is a weight ratio.
Citation Information
Patent Citations
Coating method of lithium ion battery cathode material
CN108767232A
Semi-solid lithium ion battery and preparation method thereof
CN113793976A
Battery positive electrode material and manufacturing method thereof
CN114784247A
Positive electrode material and battery
CN116195085A
Positive electrode material and battery
CN117836966A